Outside the box cardboard design now. (Black Dog Publishing Limited, 2010)
Explores the ascent of cardboard as a material within the creative industries. From its immediate association with packaging design, to its growing popularity with product and furniture designers alike, as well as its potential within art and architecture in creating intricate sculptures and large-scale installations, outside the box: cardboard now celebrates the revival of this often-overlooked material.